Mid-term outcomes of the COMMENCE trial investigating mitral valve replacement using a bioprosthesis with a novel tissueCentral MessagePerspective - David A. Heimansohn, MD; Craig Baker, MD; Evelio Rodriguez, MD; Hiroo Takayama, MD, PhD; Francois Dagenais, MD; David S. Talton, MD; Mubashir A. Mumtaz, MD; Philippe Pibarot, DMV, PhD; John D. Puskas, MD (JTCVS Open, 2023)
Objective: Novel tissue leaflets (RESILIA tissue) may improve durability of bioprosthetic heart valves. The COMMENCE trial is an ongoing prospective study to evaluate valve replacement using RESILIA tissue. This report describes mid-term outcomes in the mitral cohort of COMMENCE. Methods: Adult patients requiring mitral valve replacement were enrolled in a prospective, single-arm trial at 17 sites in the United States and Canada. An independent clinical events committee adjudicated safety events using definitions from established guidelines, and hemodynamic performance was evaluated by an independent echocardiographic core laboratory. Results: Eighty-two patients (median age 70 years) successfully underwent mitral valve replacement with the study valve. Five-year event-free probabilities for all-cause mortality, structural valve deterioration, and reoperation were 79.9%, 98.7%, and 97.1%, respectively. Hemodynamic valve function measurements were stable through the 5-year follow-up period; valvular leaks were infrequently observed and primarily clinically insignificant/mild. Conclusions: Mitral valve replacement patients implanted with a RESILIA tissue bioprosthesis had a good safety profile and clinically stable hemodynamic performance.